Respiratory Virus Infections in Asthma: Research Developments and Therapeutic Advances. - Kumar,K; Singanayagam,A; Johnston,SL (Acta Med Acad, 2020)
In this review, we discuss the latest developments in research pertaining to virus-induced asthma exacerbations and consider recent advances in treatment options. Asthma is a chronic disease of the airways that continues to impose a substantial clinical burden worldwide. Asthma exacerbations, characterised by an acute deterioration in respiratory symptoms and airflow obstruction, are associated with significant morbidity and mortality. These episodes are most commonly triggered by respiratory virus infections. The mechanisms underlying the pathogenesis of virus-induced exacerbations have been the focus of extensive biomedical research. Developing a robust understanding of the interplay between respiratory viruses and the host immune response will be critical for developing more efficacious, targeted therapies for exacerbations. CONCLUSION: There has been significant recent progress in our understanding of the mechanisms underlying virus-induced airway inflammation in asthma and these advances will underpin the development of future clinical therapies.